‘Darti voce è incontrarti nelle cose’: il canto di ritorno di Filippo Davoli tra religione e lirica - Bordoni, Michele (Incontri. Rivista europea di studi italiani, 2020)
‘Giving You a voice is crossing You in things’ The song of return in Filippo Davoli’s between lyric and religion This paper aims at investigating the phenomenon of the return of religion as well as at analysing the return of lyric poetry and French phenomenology as conceptual keys to Davoli’s literary production. The thirty-year poetic activity of Filippo Davoli (Fermo, 1965) may be defined as a very personal “return to reality” where the poet inserts daily situations as part of a wider transcendental plan, which, however, does not imply dogmatic declarations of faith. According to thematic and chronological analyses, Davoli’s poetry may constitute a parallel to contemporary expressions of religious sentiment linked to poetry. In this “initiatic-spiritual” knowledge, the poet’s mystical sentiment, or ‘Song of return’, may be preparatory to a re-reading of reality which goes beyond its material dimension. Such a double level of reading can be as well exemplified by another pivotal theme in Davoli’s production: the body and its limits express both the mere caducity of the present and its “anagogic” dimension, which consists in a further interpretation of its limits.